Effective Strategies of Volunteers in Overcoming Challenges to Build a Sustainable Community Based on Civic Engagement - Wadu, Ludovikus Bomas; Darmawan, Cecep; Anggraeni, Leni; Syaifullah, Syaifullah (Universitas Muhammadiyah Ponorogo, 2025)
This research examines effective strategies applied by volunteers in facing challenges to build sustainable communities based on civic engagement. Using a qualitative phenomenological approach, this research explores the in-depth experiences of volunteers involved in handling waste issues in Malang City. Data were collected through field observations, in-depth interviews, and documentation, which were systematically analyzed using data reduction, data presentation, and conclusion drawing. The results show that close collaboration with various stakeholders, including the government and local organizations, is key to expanding support and increasing the impact of activities. Regular internal education enhances volunteer capacity, while public campaigns and advocacy drive community awareness and policy change. Community solidarity and emotional support between volunteers play an important role in maintaining collective motivation. Other strategies include flexible time management, task delegation, and utilizing creativity in managing limited resources. Self-management is also crucial in dealing with internal challenges such as social pressure and personal expectations. Volunteers who are able to manage their emotions and stay focused on the organization's vision show higher consistency in action. This research offers practical guidance for social organizations in improving the efficiency and impact of their activities, while contributing to the academic literature on volunteer dynamics in building sustainable communities. The findings underscore the importance of innovation, collaboration and civic engagement-based approaches as a foundation for addressing increasingly complex social and environmental challenges